2012
DOI: 10.7193/dm.065.31.44
|View full text |Cite
|
Sign up to set email alerts
|

Les suremballages : des emballages superflus pour les consommateurs ?

Abstract: Les suremballages, des emballages superflus pour les consommateurs ? Les pratiques domestiques des consommateurs à l'égard des suremballages Elisa MONNOT Fanny RENIOU Résumé Actuellement, les politiques gouvernementales prônent une réduction à la source des suremballages (cartons entourant les produits sans qu'il n'y ait de regroupement d'unités primaires). Celle-ci aura des répercussions certaines sur les stratégies des industriels en termes de conception des packagings. Dans ce contexte, il paraît nécessaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
3
0
4
Order By: Relevance
“…As part of an exploratory approach, certain researchers sought to circumscribe the 'doctrine' of sustainable development (Flipo, 2004;Lauriol, 2004). Others focused on consumers in an effort to understand their representations and the meaning of responsible consumption on the one hand (Elgaaïed, 2013;Gonzales et al, 2009;Monnot and Reniou, 2012;Özçağlar-Toulouse, 2009), or to better understand their decision to purchase so-called sustainable products on the other hand (Böcker et al, 1991;Daniel, 2013;François-Lecompte and ValetteFlorence, 2006;Giannelloni, 1998;Rémy, 2004). Recent studies have also shown that resistance to products associated with sustainable development is not only linked to pricing but also to the moral stance associated with the discourse on ecology (Monnot and Reniou, 2013) or to the difficulties in identifying with these products (Gurviez and Sirieix, 2013;Pernin and Petitprêtre, 2012).…”
Section: Sustainable Developmentmentioning
confidence: 98%
“…As part of an exploratory approach, certain researchers sought to circumscribe the 'doctrine' of sustainable development (Flipo, 2004;Lauriol, 2004). Others focused on consumers in an effort to understand their representations and the meaning of responsible consumption on the one hand (Elgaaïed, 2013;Gonzales et al, 2009;Monnot and Reniou, 2012;Özçağlar-Toulouse, 2009), or to better understand their decision to purchase so-called sustainable products on the other hand (Böcker et al, 1991;Daniel, 2013;François-Lecompte and ValetteFlorence, 2006;Giannelloni, 1998;Rémy, 2004). Recent studies have also shown that resistance to products associated with sustainable development is not only linked to pricing but also to the moral stance associated with the discourse on ecology (Monnot and Reniou, 2013) or to the difficulties in identifying with these products (Gurviez and Sirieix, 2013;Pernin and Petitprêtre, 2012).…”
Section: Sustainable Developmentmentioning
confidence: 98%
“…Concerning incoming flows, because amassing large volumes of waste is a physical constraint, reducing the volume of waste coming into the home could be encouraged. In this context, both the authorities and manufacturers could encourage people to buy products with less (Monnot and Reniou, 2012), compactable or rechargeable packaging (for example in the form of labelling on products, similar to labels such as 'Made in France'). Concerning outgoing flows, more hygienic collection systems could be designed to respond to certain consumers' need for cleanliness (for example by providing containers with flaps that can be opened with the feet rather than with the hands).…”
Section: Managerial Implicationsmentioning
confidence: 98%
“…Dans une visée exploratoire, des travaux ont appréhendé la « doctrine » du développement durable (Flipo, 2004 ;Lauriol, 2004). D'autres recherches se sont focalisées sur les consommateurs pour comprendre leurs représentations et les significations liées à la consommation responsable, d'une part (Elgaaïed, 2013 ;Gonzales et al, 2009 ;Monnot et Reniou, 2012 ;), ou pour mieux appréhender leurs décisions d'achat de produits dits durables, d'autre part (Böcker, Hausruckinger et Herker, 1991 ;Daniel, 2013 ;François-Lecompte et Valette-Florence, 2006 ;Giannelloni, 1998 ;Rémy, 2004). De récents travaux montrent aussi que la résistance aux produits associés au développement durable n'est pas seulement liée à une logique de prix, mais aussi à la moralisation impliquée par les discours sur l'écologie (Monnot et Reniou, 2013) ou encore aux difficultés d'identification aux produits (Gurviez et Sirieix, 2013 ;Pernin et Petitprêtre, 2012).…”
Section: Développement Durableunclassified
“…• Significations et expériences de consommation responsable (Elgaaïed, 2013 ;Gonzales et al, 2009 ;Monnot et Reniou, 2012 ; Özçağlar-Toulouse, 2009) • Motivations, tensions et résistance à l'achat (Böcker, Hausruckinger et Herker, 1991 ;Daniel, 2013 ;Flipo, 2004 ;François-Lecompte et Valette-Florence, 2006 ;Giannelloni, 1998 ;Gurviez et Sirieix, 2013 ;Lauriol, 2004 ;Monnot et Reniou, 2013 ;Pernin et Petitprêtre, 2012 ;Rémy, 2004) • Relation consommateur-producteur (Béji-Bécheur, Fosse-Gomez et Özçağlar-Toulouse, 2005 ;Bocquet, 2013 ;Dampérat et Dussart, 2007 ;de Ferran et al, 2013 ;Dufeu et Ferrandi, 2013 ; RobertDemontrond et Özçağlar-Toulouse, 2011) • Outils marketing en faveur du développement durable (Binninger et Robert, 2013 ;Gabriel, 2003) • Diversité des formes de développement durable : frugalité, simplicité volontaire, consommateur citoyen, etc. Urien, 2006 ;Berger et Rand, 2008 ;Gomez, 2008 ;Scammon et al, 2011), à travers par exemple l'amélioration de l'information alimentaire (Chalamon et Nabec, 2013 ;Grunert, Bolton et Raats, 2011 ;Guichard et Muratore, 2011 ;Mourre, 2011 …”
Section: Bien-etre Du Consommateur (Bec) Well-being Du Consommateur (unclassified